KINERJA SISTEM DRAINASE KOTA PONTIANAK (STUDI KASUS KOTA PONTIANAK) - Suandana, Ruchiat; Nurhayati, -; Yulianto, Eko (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
The water catchment area of Parit Bansir located in Pontianak City Center, its growth has increased quite rapidly. Changes in land use in the Parit Bansir catcment area resulted in the switching of the crew function from the water catchment area into a permanent building. As  a result of changes in land use it can occur an increase in flow discharge caused by rain water flows directly to the channel without being absorbed by the soil.This study was conducted to assess the performance of drainage channels in Parit  Bansir. Main data of this research are rainfall data, tidal and flowrate data. Those data then processed with frequency analysis, design rain analysis, design discharge analysis, existing cross-sectional  analysis with HECRAS software. The results showed that 2 years return period discharge for upstream area of 2,353 km2 is 2,382 m3/sec, Parit Demang with 1,545 km2 obtained 2,138 m3/sec, Reformasi Channel with 0,883 km2obtained 1,237 m3/sec, Karya Baru channel 0,776 km2 obtained 1,866 m3/sec, Karya Baru-A.Yani Channels with 0,490 km2 obtained 1,218 m3/sec. Based on HECRAS’ hidraulics analysis, it is  known that the channel capacity . for existing water level by using the existing discharge of channel sectional capacity still can accomodate the volume of available water. For discharge of 2, 5, 10 and 20 years return period, the channel capacity is insufficient to accomodate the water volume, then the overflowing water will melt out the channel. Based on the analysis of the assessment of drainage network conditions, the performance of drainage network system in Parit Bansir obtained the weight of each channel section are : the upstream channel with 2079,40 m weighted 11,30 %, the middle channel with 2740,15 m weighted 28,64 %, and the downstream channel with 1314,54 m weighted 20,34 %. So the overall weight is 60,28 % implies that the value of drainage network system performance that can be given by Parit Bansir is 60,28 %.   Keywords:drainage channel, HEC RAS, flood, Parit Bansir